Pengaruh Pasta Gigi yang Mengandung Katekin Gambir (Uncaria gambir Roxb) Terhadap Penurunan Indeks Plak Gigi - Cimi Ilmiawati; Nurhayati Nurhayati; Bambang Bambang (Andalas Dental Journal, 2019)
Background: Dental plaque is a soft, structured, calcified layer of bacteria that accumulates and attaches to the surface of the tooth. Efforts are made to eliminate and prevent plaque on the surface of the tooth by plaque control. Plaque control can be done mechanically, chemically, or a combination of both. Chemical control is done by using toothpaste. Catechin gambier toothpaste are polyphenolic compounds that have antibacterial activity which can prevent adhesion, inhibit the enzyme activity of glucosyltransferase and kills plaque forming bacteria. Objective: To determine the effect of catechin gambier on decreasing dental plaque index. Methods: This study is a true experimental study with pre-test and post-test control group design, conducted in March – April 2019. The subjects of this study were 44 students of Faculty of Dentistry, Andalas University. The subjects were divided into two groups, one group used catechin gambier toothpaste and an control group used placebo. Plaque index was calculated using an Turesky-Gilmore-Glickman of Quingley-Hein. Data was analyzed by t-test. Results: Average of dental plaque index in treatment group was higher than placebo group. Independent t-test showed that there was significant difference of dental plaque index beetwen two groups (p<0,001). Conclusion: Catechin gambier toothpaste can reduce dental plaque index.